Laparoscopic Management of Mechanical Small Bowel Obstruction Secondary to Meckel's Diverticulum with a Double Basis. A Rare Anatomic Presentation - Mariani, Aurora; Siddiqui, Mohammed; Boulard, Nicolas; Berrebi, Dominique; Bonnard, Arnaud (European Journal of Pediatric Surgery Reports, 2020)
Meckel's diverticulum (MD) is the most common congenital abnormality of the gastrointestinal tract. Intestinal occlusion due to MD is a commonly observed consequence of intussusception or volvulus. Here, we report a case of an 11-year-old boy who presented to the emergency department with acute abdominal pain, bilious vomiting, and abdominal rebound tenderness. Computed tomography scan concluded a diagnosis of intestinal occlusion with no apparent cause. The patient was submitted to diagnostic laparoscopy, and mechanical occlusion by the permeable Meckel with double base was identified. A diverticulectomy by staplers was performed, and occlusion was alleviated. MD is a rare disease (for only 0.3–2.9% of the general population), and only 4.2 to 9% of patients diagnosed with MD have associated complications. MD can be a large base or a narrow base, with a mesodiverticular band but the diverticulum is usually a blind recess. In our case, the tube connected two intestinal segments. To the best of our knowledge, we have reported the first case of an MD-like permeable tube with a double basis.
Keywords: Meckel's diverticulum; minimal invasive surgery; laparoscopy; omphalomesenteric duct; intestinal obstruction